Performance of Islamic Political Parties in Indonesian Contemporary Political Practices - Sukardi Weda; Amiruddin Amiruddin (RIRAI Publisher, 2022)
The role of Islamic political party plays vital role in the development and stabilization of system of democracy in the world today (Woischnik & Müller, 2013, p. 59). The fact that almost all parties, especially Islamic political party has fight for religious aspirations and avoid criticizing controversial religious issues which shows the strength of religious influence in Indonesian contemporary political practices (Tanuwidjaya, 2010, p. 29). In this present study, we investigate whether the Islamic political parties and their political elites in Indonesia today think about their performance to fulfill people’s interests. We first examine people’s view on the role of Islamic political parties, and therefore explore their elite attitudes. Methodologically, this present study employs mix method, quantitative and qualitative research design. More specifically, this study is a case study. The case study is more appropriate for the analysis of this study. For data collection, the study utilizes the questionnaire, interview, and the documentary analysis. There are three steps of data analysis for qualitative data: reducing data, displaying data and drawing and verification. For quantitative data, the present study applies descriptive statistics to find out mean, standard deviation (SD), and percentage. The research findings indicate that the performance of Islamic political parties in Indonesia contemporary politics is still low and the Islamic political party voters are unsatisfactory on the Islamic political parties and their political elites.